Body Composition and Bone Metabolism in Young Gaucher Disease Type I Patients Treated with Imiglucerase - Parisi, Muriel Solange (2007)
Bone involvement is one of the most disabling complications in patients with type 1 Gaucher disease (GDI) and its pathophysiology is yet to be fully understood. It is well known that body composition is a determinant of bone mass. Previous reports indicating disturbance in glucose and lipid metabolism in GDI patients suggested a posible alteration in body composition in this group of patients. OBJECTIVE: To analyze body composition, bone mass and turnover in young adults with GDI receiving enzyme replacement therapy (ERT). Population: 5 women and 4 men with GDI aged (X +/- SD) 26.9 +/- 6.9 years, receiving imiglucerase in a mean dose of 53 +/- 13 IU/kg/2weeks, during 4.9 +/- 3.9 years; and 145 sex and age matched healthy adults agreed to participate in the study. All control subjects had a body mass index (BMI) between 20 and 25 kg/m2. METHODS: Total body dual X-ray absorptiometry (DXA) was used to measure body composition and bone mass. Serum creatinine, calcium, osteocalcin (BGP), and type I collagen beta carboxy-terminal telopeptide (betaCTX) were determined in patients and controls. In addition, 25 hydroxyvitamin D (25OHD), and chitotriosidase activity were measured in patients. Results: GDI patients presented statistically significant (p<0.01) lower BMI, bone mineral density (BMD), bone mineral content (BMC), lean mass (LM), and fat mass (FM), compared to controls. LM correlated positively with BMC and BMD in both groups (p<0.01). GDI patients receiving the lower dose of ERT (<60 IU/kg/2weeks) presented lower BMD values than those receiving the higher dose (> or =60 IU/kg/2weeks) (0.968 +/- 0.032 vs 1.088 +/- 0.061 g/m2, respectively, p<0.001). Mean BGP levels were similar in patients and controls, whereas betaCTX levels were higher in GDI patients (p<0.02). All patients presented deficiency levels (<30ng/ml) of 25OHD. CONCLUSIONS: Although the patients had been receiving ERT, they presented a significant diminution in all body composition parameters, the decrease was more evident in those receiving the lower dose. The reduction in bone mass was associated with an imbalance in bone turnover (increased bone resorption). The correlation between LM and bone mass, suggests that metabolic disturbance occurring in GDI patients may be indirectly responsible for bone mass reduction in GDI patients, by altering body composition